PENERAPAN MEDIA CANVA POSTER TERHADAP HASIL BELAJAR KELAS XI IPS SMA NEGERI 5 PONTIANAK - Koesnadi, Faysal; Asriati, Nuraini; Budiman, Jumardi (Universitas Tanjungpura, 2023)
The purpose of this study is to determine the impact of canva-poster media on the results of the economics coursework completed by students in grades XI and IPS at SMA Negeri 5 Pontianak. Penelitian using a quantitative sampling technique combined with the qualitative experimental research methodology. Around 60 people participated in this study's data collection, and they were divided into two groups: kelas eskperimen (for creating canva-posters) and kelas kontrol (for comparison). sumber data penelitian di SMA Negeri 5 Pontianak, kelas XI IPS 1 dan 2 as eksperimen mata pelajaran ekonomi, diambil dari data dengan nilai terendah as kelas eksperimen. Data collection methods involving classroom observation, as well as pretest and posttest testing. Variables with the word